Relationships of otolith dimension with body length of European eel Anguilla anguilla (Linnaeus, 1758) from Adriatic catchment of Montenegro - Kanjuh, Tamara (Array, 2018)
This study examined the relationship between the sagittal otolith morphometric variables (length, height and weight) and body growth of the European eel. Eels that were studied ranged in total length from 11.2 to 79.5 cm. The relationships between the sagittal otolith variables and fish somatic growth were described with a non-linear function. The resulting coefficients of determination \((r 2)\) ranged from 0.782 to 0.914. The variable most strongly related to fish size was found to be the sagittal otolith length (OL) with 91.4 % of the variability. The results of this study provide the first comprehensive data regarding the relationship between the sagittal otolith morphometric variables with the body length of Anguilla anguilla.